Infuencing processed composite material priperties on acoustic emission - Филоненко, Сергей Федорович (Eastern-European Journal of Enterprise Technologies, 2015)
It is quite difficult to prove the informativeness of the parameters for acoustic emission during control, diagnostics and monitoring the technology of composite materials tooling as well as the parameters optimization. We have considered the resulting acoustic emission signals at tooling the composite material for a mechanical model of destroying its surface layer. We have studied the impact of a parameter determined by the properties of the destroyed surface layer of composite material on amplitude characteristics of the acoustic emission. We have proved that the influencing parameter does not alter the nature of the formed acoustic radiation. The resulting acoustic emission signals are continuous but very ragged. A rising influencing parameter leads to falling amplitude characteristics of the resulting acoustic emission signals––with an average amplitude rate, its standard deviation, and dispersion. At a general decrease of the amplitude parameters of acoustic emission, the rising influencing parameter mostly affects dispersion of the average resulting signal amplitude. The obtained results show that optimization of parameters for the technology of composite materials tooling (where composite materials have various physical and mechanical characteristics) as well as devising methods of control, diagnostics and monitoring of such processes as an informative parameter requires to analyze the alteration patterns of dispersion of the average resulting signal amplitude.